Rantai Pasar Ikan Cakalang Asap Pada Masa Pandemi Covid-19 Dan New Normal Di Kota Jayapura - Tuhumena, lolita; Rumahorbo, Basa T. Rumahorbo; Rewang, Grisella M. S. P.; Pirhel; Mandey, Vera K. (Cenderawasih University, 2023)
The conditions of the Covid-19 pandemic that occurred in 2019-2021 affected the marketing system for Smoked Skipjack. Therefore, the research will be conducted to find out the marketing channels and marketing margins of Smoked Skipjack during the Covid-19 pandemic and the new normal. The research lasted for 6 months at the Mama-mama Papua Market, Hamadi Market, and Cikombong Market. This research method is purposive sampling and be analyzed using descriptive qualitative and quantitative. Based on the research results, it was found that the marketing channel started with fishermen in Dock 9, Jayapura City, who sold their catch to collectors, then collectors sold it to traders who processed fish into smoked fish and smoked fish traders sold it directly to consumers. During the Covid-19 pandemic, the market that had the lowest marketing margin was the Cikombong Market and the highest margin was the Hamadi Market. During the new normal, the highest marketing margin occurred at the Hamadi Market and the lowest was the Cigombong Market, followed by the Mama-Mama Papua Market. During the Covid-19 pandemic and the new normal, efficient markets were the Papua Mama-mama Market, Hamadi Market and Cigombong market, because had <5% efficiency.Then during the new normal, marketing efficiency at Hamadi Market, Papua Mama-mama Market and Cigombong Market were efficient because it had <5% efficiency.